Visual outcomes of medical and surgical modalities in secondary glaucomas (inflammatory vs pigmentary) compared to primary open-angle glaucoma. A multi-factorial comparative study - Adeel Chaudhry, Fareeha Mirza, Tariq Pervaiz Khan, Fakhar Humayun, Fahd Kamal Akhtar, Muhammad Imran Ali (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Secondary glaucomas, particularly inflammatory glaucoma (IG) and pigmentary glaucoma (PG),demonstrate greater clinical variability and treatment complexity compared to primary open-angleglaucoma (POAG). This prospective, multifactorial cohort study